The evidence base on the environmental, economic and social outcomes of agroforestry is patchy—An evidence review map - Köthke, Margret; Ahimbisibwe, Vianny; Lippe, Melvin (Frontiers in Environmental Science, 2022)
Agroforestry is often seen as a panacea that offers multiple environmental, economic, and social benefits. However, the validity of generalized statements on agroforestry outcomes is doubtful because the evidence base is unclear. Systematic reviews and meta-analyses exist on the topic in addition to many case studies that address specific outcomes of individual agroforestry practices at different sites. However, the overall picture of available scientific evidence on agroforestry outcomes remains opaque due to the wide diversity of existing agroforestry practices, outcome indicators, and spatial locations. To clarify whether and in which areas the research landscape allows conclusions to be drawn about the potential benefits or drawbacks of agroforestry compared to other land uses, an evidence review map was created for the purpose of this study. Based on a systematic literature search and screening, 64 systematic review articles were finally identified that summarize ecological, economic, or social outcomes of at least one agroforestry practice compared to another land use as control. The thematic and spatial coverage of the systematic reviews on agroforestry outcomes is mapped to identify density and research gaps in the evidence base. Moreover, the comprehensibility of the study selection for each identified systematic review is critically assessed. The resulting evidence review map discloses a solid evidence base for environmental outcomes and productivity aspects of individual agrisilvicultural practices, as well as for agroforestry systems when considering an aggregate level. However, the outcomes of individual silvopastoral and agrosilvopastoral practices have been less studied in the literature. A global coverage at the level of individual agroforestry practices is only available for impacts on climate change mitigation. Major research gaps were identified for systematic analysis of social outcomes of all agroforestry types. The results of the evidence mapping highlight further research needs, but also urge for caution in making generalized statements about the benefits of agroforestry.